Pollution Status of Indian River and Water Quality Parameters - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2019)
A solution to the country's water dilemma is urgently required in the modern day. It is imperative that the country find a way to increase the amount of water that can be used for drinking. A steady supply of high-quality drinkable water is essential to achieving any kind of progress in the economy or in the political arena. As a result, it's obvious that river revitalization efforts should be spread out across the country. Furthermore, we will need to collect rainwater wherever it falls in order to ensure local water security and recharge each well. The present study looks at India's water resources from two angles: pollution in river basins and the necessity for river rejuvenation projects to be carried out in India. The results are mixed. For example, river rejuvenation and water resources in India have been harmed by pollution from numerous sources and types in river basins, so this is the basis for this proposal.